Particle flux composition and environmental drivers near cold-water coral mounds in the Campos Basin - Sousa, Janaina Santana de [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
The downward flux of particulate organic matter (POM) sustains most deep-sea ecosystems, including cold water coral (CWC) reefs and banks. Using sediment-trap time series, chemical analyses, artificial intelligence, and physical oceanographic sensors, we characterized the composition and drivers of sinking particles reaching CWC banks in the Campos Basin (SW Atlantic). Analysis of > 46,000 particles collected at two depths (625 and 925 m), with 12–19-day integrated samples, revealed fluxes spanning over two orders of magnitude, from ~300 to ~15,000 particles m⁻² day⁻¹. Detritus dominated the sinking material (60–90%), punctuated by brief intervals in which pelagic or benthic organisms accounted for more than half of the flux, indicating marked but short-lived shifts in particle assemblage. Chemical composition fluctuated mainly through changes in carbon content (0.21-1.11%), while nitrogen content remained comparatively stable (0.02% to 0.08%), pointing to changes in material composition rather than degradation state. Although linear correlations between particle flux and environmental variables were weak, time-series inspection showed that the largest detrital pulse coincided with a sharp increase in turbidity (76.88 NTU) and was followed by a rise in chlorophyll-a, suggesting that transient water-column processes are linked to vertical particle delivery even when not resolved statistically. This lack of statistical resolution likely reflects a temporal mismatch between the short-term (hourly-daily) variability of water-column processes and the integrative nature of sediment traps (weeks), smoothing short-lived events that drive particle flux. We demonstrate that CWC habitats in the Campos Basin are sustained by a dual-particle supply regime: a constant deposition of low-quality detritus interspersed with short-lived, potentially more nutritious pulses. Recognizing this temporal heterogeneity is critical for understanding the energy pathways that support deep-sea biodiversity.
Composição do fluxo de partículas e seus fatores ambientais associados nas proximidades de montes de corais de águas frias na Bacia de Campos
Keywords: Cold-water corals; Particle flux; Deep sea; Southwest Atlantic; Sediment trap; Recifes de coral; Partículas; Atlântico, Oceano